Ex uno plura : state constitutions and their political cultures - McHugh, James T., 1961- (SUNY series in American constitutionalism., 2003)
"State Constitutions have become increasingly important in light of recent trends in jurisprudence that favor decentralizing the American federal system. Ex Uno Plura uses a political culture approach to explore eight state constitutional traditions. McHugh argues that state jurisprudence is not merely a reflection of the process, values, and decisions found at the federal level, especially through the influence of the Fourteenth Amendment. A close examination of separate state constitutions, including their origins, sociopolitical cultures, and jurisprudence, reveals historically, culturally, and philosophically unique characteristics, each of which will contribute to the ongoing debate concerning American judicial federalism. The states included are Alaska, California, Georgia, Hawaii, Louisiana, Utah, Vermont, and Wyoming."--Jacket